Biomimetic tumor cell membrane-camouflaged nanomicelles for synergistic chemo-immunotherapy of Triple-negative breast cancer - Xiaoman Xu; Yunmei Song; Mingli Li; Fengxi Liu; Huiwen Zhang; Jingxia Xu; Juwei Gao; Yanna Lv; Bo Zhang; Sanjay Garg (Materials Today Bio)
Triple-negative breast cancer (TNBC) remains a clinical challenge due to its aggressive nature. Conventional chemo-immunotherapy suffers from poor tumor targeting and systemic toxicity, necessitating advanced delivery systems for synergistic drug combinations. This study constructed a biomimetic nanodrug delivery system by coating nanomicelles with 4T1 tumor cell membranes. This strategy leverages the homologous targeting ability of tumor cell membranes to improve the accumulation of nanomicelles within TNBC tissues. The cytotoxic agent bortezomib (BTZ) and the immune modulator resiquimod (R848) were encapsulated individually and co-administered to investigate the synergistic chemo-immunotherapeutic efficacy in TNBC treatment. The biomimetic nanomicelles exhibited excellent biocompatibility and homologous targeting capacity, significantly enhancing drug delivery efficiency at the tumor site. In vitro studies demonstrated that biomimetic nanomicelles effectively induced tumor cell apoptosis, repolarized tumor-associated macrophages toward the M1 phenotype and promoted dendritic cell maturation. In vivo experiments further confirmed that the biomimetic nanomicelles markedly inhibited tumor growth and metastasis, enhanced antitumor immune responses, and exhibited strong synergy with BTZ to improve overall therapeutic outcomes in TNBC. This dual-action biomimetic nanomicelles delivery platform achieved efficient chemo-immunotherapeutic synergy and represents a promising strategy for targeted treatment of TNBC, with strong potential for clinical translation.